A load shedding scheme for DG integrated islanded power system utilizing backtracking search algorithm - Khamis, Aziah; Shareef, Hussain; Mohamed, Azah (Ain Shams University, 2018)
In a dispersed generation (DG) integrated distribution system, several technical issues should be resolved if the grid disconnects and forms an islanded system. The most critical challenge in such a situation is to maintain the stability of the islanded system. The common practice is to reject several loads through a load shedding scheme. This study introduces a development of an optimal load shedding scheme based on backtracking search algorithm (BSA). To handle this optimization problem, a constraint multiobjective function that considers the linear static voltage stability margin (VSM) and amount of load curtailment is formulated. It also handles the load priority and various operating conditions of DGs. The performance of the proposed load shedding scheme was evaluated through an extensive test conducted on the IEEE 33-bus radial distribution system with four DG units considering several scenarios such as load shedding under various operating points and at various islands using the MATLAB software. Moreover, the effectiveness of the proposed scheme was validated by comparing its results with those obtained using the genetic algorithm (GA). The optimization results indicate that the proposed BSA technique is more effective in determining the optimal amount of load to be shed in any islanded system compared with GA.